PRAKTIK KOTOR BISNIS INDUSTRI FARMASI DALAM BINGKAI INTELLECTUAL CAPITAL DAN TELEOLOGY THEORY - Sigit Hermawan (Jurnal Akuntansi Multiparadigma, 2013)
Abstract: Dirty Practice of Pharmaceutical Industry in The Frame of Intellectual Capital and Teleology Theory. The aim of study is to explore ‘dirty’ business practice of pharmaceutical industry in Indonesia. The result shows that there were bad practices there, ranging from nonconforming raw material selection, illegal medicine ingredient, keeping of rejected and destroyed products and misapropriation of herbal medicine that contained chemicals material. The ethical violation also occurred in products marketing by engaging collaboration or ‘private’ contract with doctors, hospitals and drugstores. In the frame of IC, those practices show that the empowerment of IC are not implemented appropriately. Meanwhile, based on teleology theory, those dirty operations were included in ethical egoism that should be changed into utilitarianism behavior.Abstrak: Praktik Kotor Bisnis Industri Farmasi dalam Bingkai Intellectual Capital dan Teleology Theory. Tujuan penelitian ini adalah untuk menggali praktik kotor bisnis industri farmasi Indonesia. Hasil penelitian menunjukkan bahwa terdapat praktik kotor di sana. Bentuknya terentang mulai dari pemilihan bahan baku tak sesuai, permainan komposisi obat, penyimpanan produk rusak dan afkir hingga penyalahgunaan obat herbal yang disisipkan bahan kimia. Pelanggaran etika juga terjadi pada pemasaran obat yakni dengan melakukan kerjasama atau kontrak pribadi penjualan obat tertentu dengan dokter, rumah sakit dan apotek. Praktik-praktik seperti ini dalam tinjauan Intelectual Capital menunjukkan adanya pengelolaan dan pemberdayaan IC yang tidak benar. Berdasar tinjauan teleology theory, praktik tersebut termasuk dalam perilaku egoisme etis yang harus diubah menjadi perilaku utilitarianisme.